Analysis of Layout of Yogyakarta Airport Railway Station and Its Integration with Tugu Railway Station - Prabendra A. Atmakusuma; Danang Parikesit (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
The government of Indonesia plans to build new airport that is located in Temon Sub-district, Kulon Progo Regency. However, the distance of the airport is quite far from the center of Yogyakarta City, therefore it is necessary to build a railway that functioned as a connector. The operating airport railway would then means an Airport Railway Station that is located in the center of Yogyakarta City, in order to accommodate the fluency of railway operation. This paper is intended to give information on the layout design, and also the location of Airport Railway Station in the center of Yogyakarta City. To generate layout of railway that is integrated with Tugu Railway Station of Yogyakarta, the methods used were: determining the station classification, determining the zone, the circulation and wayfinding, so that the passengers could move fluently. Based on the analysis result, the Airport Railway Station has categorized a large class station, with its location was designed separately from the Tugu Railway Station, but integrated with 52 meters long tunnel in south of the Airport Railway Station. The layout design of the Airport Railway Station was designed to be two levels and with two platforms with land necessity of 9100 m2, and was predicted to serve 515 passengers per rush hour.